Rehabitar la Montaña: strategies and processes for sustainable communities in the mountainous periphery of Medellín - Claghorn, Joseph; Orsini, Francesco Maria; Echeverri Restrepo, Carlos Alejandro; Werthmann, Christian (Revista Brasileira de Gestão Urbana, 2017)
Thousands of poor, marginal communities’ residents die due to landslide events every year. The quick urbanization of mountainous areas, combined with an increased frequency of landslide events induced by heavy rains due to climate change, is leading to increased deaths year after year, and the problem will only get worse. Landscape Architects, trained to analyze and intervene in situations with complex natural and social territorial dynamics, are in position to make positive contributions to mitigating risks in such situations. A collaborative effort between a team of landscape architects from Germany and Urbanists in Medellín Colombia is carrying out a four-phased research and implementation proposal to anticipate and mitigate risk in low-income settlements on Medellín’s urban periphery. They propose five pilot projects to test risk mitigation strategies through monitoring and early warning systems, drainage improvements, urban agriculture, slope forestation, and developing sites with the supplied services.